Numerical Modeling of CuInxGa(1-x)Se2/WS2 Thin Solar Cell with an Enhanced PCE - Belhadji, Youcef (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Designing thin film solar cells with high and stable output performance under different operating points remains a large area of research. In the context of Chalcopyrite-based solar cells (CuInxGa(1-x)Se2) where the buffer layer is CdS, great progress has been made but research is still underway to optimize their performance. Besides the environmental concerns and limiting factors of CdS material, the use or combination of new materials like ZnS, ZnSe and WS2 as a buffer layer is solicited. Due to these attracted optical and crystallographic properties, Tungsten Disulfide: WS2 is solicited during the last years. Through numerical simulation, we investigate in this work the dc parameters of CuInxGa(1-x)Se2/WS2 solar cell with reduced buffer layer thickness of 30 nm. Considering the presence of neutral and divalent defects in the absorber layer, simulations are performed under the impact of temperature, concentration of charge carriers in WS2 layer and light spectrum change. The divalent defects taken into account are: double donors / acceptors and amphoteric having a Gaussian distribution. For more calculation precision and in order to obtain the desired performance of the solar cell, the impact of series and shunt resistors is also considered. In comparison with results reported in previous works, carried out on the CuInxGa(1-x) Se2/WS2 solar cell, a remarkable improvement in the performance of the solar cell is achieved. When temperature increase by 10K, the short circuit current and Â open circuit voltage are enhanced by 0,05mA/cm2 and 0,0022 respectively. The optimal values of the solar cell parameters obtained in this study are: Jscâ‰ˆ 31.0683 (mA/cm2), Voc=1.0173 (V), PCE = 26.72 % and FF=84.54%.